Colonization by arbuscular mycorrhizal fungi improves salinity tolerance of eucalyptus (Eucalyptus camaldulensis) seedlings - Klinsukon, Chaiya; Lumyong, Saisamorn; Kuyper, Thomas W.; Boonlue, Sophon (Scientific reports, 2021)
Soil salinity affects soil quality and reduces plant performance. Arbuscular mycorrhizal fungi (AMF) can enhance the tolerance of plants under salinity stress. Cultivation of eucalyptus ( Eucalyptus camaldulensis ), which exhibits high water use efficiency, is possible in saline areas to produce raw materials for the pulp industry. We determined the effects of arbuscular mycorrhizal fungi (AMF) on the growth and survival of eucalyptus seedlings under saline conditions. Three different clones of eucalyptus seedlings were pre-inoculated with three salt-tolerant AMF species, namely Glomus sp.2, Gigaspora albida and G. decipiens , and without pre-inoculation. The seedlings were grown in a greenhouse for 45 days. They were then transferred to individual pots, filled with field soil and subsequently treated with NaCl solution until electro-conductivity (EC) reached 10, 15 and 20 dS m −1 . They were watered for 90 days under nursery conditions. The results show that increased salinity levels reduced plant performance, fractional AMF root colonization, spore number, and eucalypt K/Na ratio. AMF significantly increased chlorophyll and decreased leaf proline concentrations by more than 50% and 20% respectively and increased the K/Na ratio three- to six-fold compared with non-inoculated plants. Pre-inoculation with AMF before outplanting also improved plant performance by more than 30% under salinity stress compared to non-inoculated plants. We conclude that AMF can alleviate the negative impacts of salinity on plant physiological and biochemical parameters.